A global map of species at risk of extinction due to natural hazards - Gonçalves, Fernando [UNESP]; Farooq, Harith; Harfoot, Mike; Pires, Mathias M. [UNESP]; Villar, Nacho [UNESP]; Sales, Lilian; Carvalho, Carolina [UNESP]; Bello, Carolina [UNESP]; Emer, Carine [UNESP]; Bovendorp, Ricardo S. [UNESP]; Mendes, Calebe [UNESP]; Beca, Gabrielle [UNESP]; et al. (Proceedings of the National Academy of Sciences, 2024)
An often-overlooked question of the biodiversity crisis is how natural hazards contribute to species extinction risk. To address this issue, we explored how four natural hazards, earthquakes, hurricanes, tsunamis, and volcanoes, overlapped with the distribution ranges of amphibians, birds, mammals, and reptiles that have either narrow distributions or populations with few mature individuals. To assess which species are at risk from these natural hazards, we combined the frequency and magnitude of each natural hazard to estimate their impact. We considered species at risk if they overlapped with regions where any of the four natural hazards historically occurred (n = 3,722). Those species with at least a quarter of their range subjected to a high relative impact were considered at high risk (n = 2,001) of extinction due to natural hazards. In total, 834 reptiles, 617 amphibians, 302 birds, and 248 mammals were at high risk and they were mainly distributed on islands and in the tropics. Hurricanes (n = 983) and earthquakes (n = 868) affected most species, while tsunamis (n = 272), and volcanoes (n = 171) affected considerably fewer. The region with the highest number of species at high risk was the Pacific Ring of Fire, especially due to volcanoes, earthquakes, and tsunamis, while hurricane-related high-risk species were concentrated in the Caribbean Sea, Gulf of Mexico, and northwestern Pacific Ocean. Our study provides important information regarding the species at risk due to natural hazards and can help guide conservation attention and efforts to safeguard their survival.
Keywords: conservation strategies; earthquake; hurricane; tsunamis; volcanoes